2022
DOI: 10.2147/dddt.s326332
|View full text |Cite
|
Sign up to set email alerts
|

Promising Natural Products in New Drug Design, Development, and Therapy for Skin Disorders: An Overview of Scientific Evidence and Understanding Their Mechanism of Action

Abstract: The skin is the largest organ in the human body, composed of the epidermis and the dermis. It provides protection and acts as a barrier against external menaces like allergens, chemicals, systemic toxicity, and infectious organisms. Skin disorders like cancer, dermatitis, psoriasis, wounds, skin aging, acne, and skin infection occur frequently and can impact human life. According to a growing body of evidence, several studies have reported that natural products have the potential for treating skin disorders. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 260 publications
(440 reference statements)
1
26
0
Order By: Relevance
“…This may also be related to the fact that, in contrast to the Gujjar and Bakarwal populations, which frequently intermarry, the Kashmiri community is strongly endogamous due to its geographical location. Similar results were reported by [ 8 ] from the North-West Frontier Province, Pakistan, [ 33 , 50 , 51 ] and from the Western Himalayas of Jammu and Kashmir.…”
Section: Resultssupporting
confidence: 89%
“…This may also be related to the fact that, in contrast to the Gujjar and Bakarwal populations, which frequently intermarry, the Kashmiri community is strongly endogamous due to its geographical location. Similar results were reported by [ 8 ] from the North-West Frontier Province, Pakistan, [ 33 , 50 , 51 ] and from the Western Himalayas of Jammu and Kashmir.…”
Section: Resultssupporting
confidence: 89%
“…Phyto-compounds, extracted from plants, are generally characterized by reduced side effects in long-term treatments and low production costs. In addition, complementary approaches based on natural compounds are gaining increasing attention due to superior patient compliance compared to traditional synthetic drugs [27][28][29]. Our data have shown that CINNA administration is able to reduce LPS-induced IL-1β and IL-6 release in human PBMCs, and consistently also in THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 70%
“…Fruits are rich in antioxidants and are considered to be more antioxidant than vitamin C [78] . Natural products, because of their antioxidant nature can be beneficial in skin disorders through their antimicrobial, wound healing, and antiinflammatory properties [79] . The role of amla phytochemicals in alleviating eye problems, skin disorders, and allergy is yet to be determined; however, antioxidants/antiinflammatory phytochemicals in amla can be beneficial in eye disorders like conjunctivitis and inhibit progress of diabetic retinopathy [80] .…”
Section: Resultsmentioning
confidence: 99%